The Influence of Digital Marketing, Brand Awareness, and Religiosity on Interest in Using Bank Syariah Indonesia Services Among Generation Z in Pamekasan Regency - Sheril Fardiana; Irmayanti Hasan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze how digital marketing, brand awareness, and religiosity influence Generation Z’s intention to apply Bank Syariah Indonesia (BSI) services in Pamekasan Regency. A causal-descriptive design utilizing quantitative methods was employed. Purposive sampling served as the method for selecting participants. The study involved 100 Generation Z respondents from the districts of Tlanakan, Pamekasan, Pademawu, Larangan, and Galis. Research data were collected after the distribution of online questionnaires using Google Forms. The results indicated that, whether considered individually or collectively, digital marketing, brand awareness, and religiosity each have a positive and meaningful effect on the level of interest in applying BSI services.